Heat Transfer in Nanofluids-A Review - Das, Sarit Kumar; Choi, Stephen U. S.; Patel, Hrishikesh E. (Heat transfer engineering, 2006)
Suspended nanoparticles in conventional fluids, called nanofluids, have been the subject of intensive study worldwide since pioneering researchers recently discovered the anomalous thermal behavior of these fluids. The enhanced thermal conductivity of these fluids with small-particle concentration was surprising and could not be explained by existing theories. Micrometer-sized particle-fluid suspensions exhibit no such dramatic enhancement. This difference has led to studies of other modes of heat transfer and efforts to develop a comprehensive theory. This article presents an exhaustive review of these studies and suggests a direction for future developments. The review and suggestions could be useful because the literature in this area is spread over a wide range of disciplines, including heat transfer, material science, physics, chemical engineering and synthetic chemistry.